Effect of the African Traditional Medicine, Sutherlandia frutescens, on the Bioavailability of the Antiretroviral Protease Inhibitor, Atazanavir. (12th December 2013) - Müller, Adrienne C.; Skinner, Michael F.; Kanfer, Isadore
Abstract : The objective of this study was to investigate the effect of Sutherlandia frutescens (SF) on the bioavailability of atazanavir (ATV) in twelve healthy male subjects. During Phase I (Day 1), subjects ingested a single dose of ATV and blood samples were drawn before dose and at 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 5.0, 6.0, 9.0, 12, 18, and 24 hours after dose. From Day 3 to Day 14, a single dose of milled SF was administered twice daily to each subject. During Phase II, Day 15, subjects ingested single doses of ATV and SF. Blood samples were drawn as previously described. Plasma was harvested from blood samples and the concentration of ATV therein was determined. For each phase, the mean ATV plasma concentration-time profile was plotted and the means of AUC 0–24 and C m a x for ATV were computed. The geometric mean ratios and confidence intervals (CIs) for C m a x and AUC 0–24 hr were 0.783 (0.609–1.00) and 0.801 (0.634–1.01), respectively. The CIs for both PK parameters fell below the limits of the "no-effect" boundary, set at 0.8–1.25, indicating that SF significantly reduced the bioavailability of ATV. This may potentially result in subtherapeutic plasma concentrations and thus reduced anti-HIV efficacy of ATV.